ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PENDAPATAN PETANI PADI SAWAH (ORYZA SATIVA L) DI DESA LEGU WODA KECAMATAN MAGEPANDA KABUPATEN SIKKA - Selfianus; Anggriani, Yohana (Jurnal Biogenerasi, 2024)
This research aims to determine how much influence the use of production factors has, determine the level of allocative efficiency, and determine the income received by rice farmers in one planting season in Legu Woda Village, Magepanda District, Sikka Regency. Location selection was carried out purposively based on land area and rice production results. The analytical method used is multiple linear regression analysis with the Cobb-Douglass function, allocative efficiency analysis, and farming income analysis. The research results show that simultaneously, all X variables influence rice production and partially, all X variables influence rice production. The regression results show that the R Square (R²) value is 0.626 or 62.6%. This means that 62.6% of rice production is explained by variable X, while 37.4% is explained by other variables. The research results show that the average income received by farmers is IDR 8,501,984. The results of the allocative efficiency analysis show that the factors of land area, fertilizer, seeds, labor, pesticides and water are not optimal.